PENERAPAN METODE INVESTIGASI KELOMPOK DALAM PEMBELAJARAN MENULIS TEKS EKSPLANASI MELALUI PENELITIAN TINDAKAN KELAS - Belinda Tri Ari Arva; Sumarwati Sumarwati; Sri Hastuti (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The purpose of this study isto increase motivation and ability writetext explanation on student class XI A P 1 SMK N 1 Surakarta with apply method group investigation. This is classrrom action research which carried out in two cycles, each cycle consisting of planning, action, observation, and reflection. The results showed that through the application of methods group investigationcan increase motivation and potentiality write explanatory texts in class XI A P 1 SMK N 1 Surakarta from action practice to the first cycle and from the first cycle to the second cycle. Motivation students and in ability to write explanation text increase although not optimal yet there are still some deficiencies both from the teacher and student factors and need to be improved by the second cycle. The conclusions are: (1) implementation method group investigation enhancing motivation on student, (2) application of group investigation methods enhancing the ability to write explanatory text on students with concrete steps taken.